نظرية الذكاءات المتعددة( دراسة نظرية ) (Journal Of Educational and Psychological Researches, 2016)
Intelligence is the production of nervous system function and it's contents memory and creative thinking and understanding and other processes. It's a general cognitive ability and it's a concept. It's essential for good judgment and reasoning, there's an argument about definition of intelligence, is it one ability or multiple abilities. Multiple intelligences theory presented by (Gardner 1983) view intelligence as composing from six types of intelligences: (1) linguistic. (2) mathematical. (3) visual – spatial. (4) musical. (5) bodily – kinesthetic. (6) personal. Present research has reached to several conclusions. Most important one is that multiple intelligences theory is based on the conception of distinct varieties of intelligences not just one intelligence and this theory has large role in education process.